Rossi's principles of transfusion medicine - Simon, Toby L.; Gehrie, Eric A.; McCullough, Jeffrey, 1938-; Roback, John D., 1961-; Snyder, Edward L. (Edward Leonard), 1946-; Ohio Library and Information Network (Hoboken, NJ : John Wiley & Sons, Inc., 2022)
"Prehistoric man left drawings of himself pierced by arrows.1 This means he was as aware of blood as he was of his own limbs. The flint implements he used as tools and weapons distinguished him from other creatures and contributed to the violence of his era. As he hunted food and fought enemies, he observed bleeding and the properties of blood. A cut, received or inflicted, yielded a vivid red color. If the cut was shallow, there was little blood. But if the cut was deep, a red torrent flowing from the stricken victim quickly led to death, with shed blood congealed and darkening in the sun. Fatal hemorrhage was commonplace. Nonetheless, the sight must have been fearful and possibly existential as life flowed red out of the body of an enemy or a wounded animal. 2 It is no wonder, then, that at the dawn of recorded history, blood was already celebrated in religious rites and rituals as a life-giving force"--
Keywords: Blood -- Transfusion; Blood cells; Blood Transfusion; Blood Cells; Blood Grouping and Crossmatching; Transfusion Reaction; Electronic books